POLA SEBARAN SPASIAL BIOMASSA DI AREAL REVEGETASI BEKAS TAMBANG NIKEL - Witno Witno; Nining Puspaningsih; Budi Kuncahyo (Universitas Andi Djemma Palopo, 2019)
The aim of this study was to identify the spatial pattern of biomass distribution in the revegetation of the post-mining area in PTVI. The nearest neighbour analysis method by comparing the distance of an individual was used to determine the spatial biomass distribution pattern in the post nickel mining revegetation area of PTVI. The nearest neighbour analysis was used to explain the distribution pattern of locations using a calculation that considers the distance, number of locations and acreage. This analysis produced a final result in the form of an index ranging from 0 until more than 1. It can be explained as NNI 1, clustered spatial pattern, NNI = 1, random spatial pattern and NNI 1 dispersed spatial pattern. This research was found that there are clustered (K1, K2, K3) and dispersed patterns (K4) of biomass spatial distribution patterns in PTVI’s post nickel mining revegetation area.Keywords: post-mining, revegetation, biomass, spatial distribution pattern